HEMODIALYSIS IN UKRAINE (2006-2015 YEARS) - Kolesnyk, M. O.; Saidakova, N. O.; Kozlyuk, N. I.; Nikolaenko, S. S.; Snisar, L.M. (Ukrainian Journal of Nephrology and Dialysis, 2017)
We used the data of “National Register of CKD Patients ” which is formed annually by SI “Institute of Nephrology NAMS of Ukraine”. The results demonstrate the low level of availability of medical care